Cold Compress Therapy Against Muscle Stiffness in Patients with Hypokalemia - Yanti Srinayanti; Andika Abdul Malik; Yudisa Diaz Lutfi Sandi (Inspirasi Foundation, 2021)
Introduction: Progressive muscle stiffness, especially in the proximal muscle groups of the lower limbs, in patients with hypokalemia paralysis causes recurrent acute attacks. Objective: The purpose of this study was to describe the results of applying cold compress therapy as an effort to reduce muscle stiffness in hypokalemia paralysis patients. Method: This research used the design of the Evidence Based Nursing implementation process consisting of: (1) compiling questions (Problem/population, Intervention, Comparison and Outcome) to be implemented, (2) tracing evidence related to cases to be discussed, (3) assessing the evidence presented. obtained in stage two, and (5) evaluation of the implementation of Evidence Based Nursing. Result: Giving cold compress therapy intervention, the visual analog scale decreased from level 7 (very severe scale) or scale 1 (mild pain), the patient said that significant decrease in pain scale after cold compress therapy. Conclusion: Cold compress therapy for 15 minutes can reduce the scale of pain and muscle stiffness.